Developing Educational Game Application for Chemistry Periodic Table - Wijaya, Antonius Gunawan; Nugroho, Erdhi Widyarto; Harnadi, Bernardinus (Soegijapranata Catholic University, 2024)
Chemistry is one of the elective subjects and cross-interest subjects taught at the high school level or equivalent secondary education. The periodic table is a chart that contains the names and types of chemical elements grouped according to their similarities and properties. In current learning, more than 75% of high school students still face difficulties in naming elements in the periodic table, especially in understanding the periodic system and the regularities of the chemical properties of these elements. Conventional teaching methods often bore students, and there is a need for engaging learning media to enhance the learning outcomes. With the increasing use of Android gadgets, where students use Android devices for classes, learning through games on Android can be effective. This game is designed using Unity in 2D format and is built for the Android platform, specifically for chemistry education in grade X of high school. The chosen game design method for this application is the waterfall method. The result of this research is the game